The Effect of Service Quality and Ease of Use on Repurchase Interest Through Consumer Satisfaction as an Intervening Variable - Kurniawan, Bagas; Marka, Mira Meilia (The Graduate School of Sahid University, 2025)
This study aims to analyze the effect of service quality and ease of use on repurchase intention through consumer satisfaction as an intervening variable on Lazada application users in Kudus Regency. The method used in this study is a quantitative method,The sample used in this study was 100 respondents using purposive sampling technique. The results of this study state that service quality has a positive and significant effect on consumer satisfaction, ease of use has a positive and significant effect on consumer satisfaction, service quality has a positive and significant effect on repurchase intention, ease of use has a positive and significant effect on repurchase intention, consurmer satisfaction has a positive and significant effect on repurchase intention